2020
DOI: 10.1186/s41155-020-00141-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying intervention mapping approach to a program for early intervention in first-episode mental crisis of a psychotic type

Abstract: The holotropic mind perspective, an integral part of the framework of transpersonal psychology, has been considered a revolutionary approach to a certain spectrum of experiences in Non-ordinary states of consciousness (NOSC) which conventional approaches tend to treat indiscriminately as pathological processes, because PHM recognizes in these experiences their healing and evolutionary potential. This article describes the needs assessment, implementation, and evaluation of an experiential and educational progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This protocol is unprecedented and of great relevance, as some studies [ 24 , 25 ] have already demonstrated that the implementation of clinical deterioration evaluation directly impacts nurses in three areas of competence: (1) evaluation and care of patients (through the detection of clinical deterioration and development of skills and knowledge); (2) referring patients (through knowledge of the language and lines of communication in the referral process and deciding whether to seek help); and (3) coping experiences. Studies have also demonstrated that most patients who required hospitalization in intensive care units or who experienced cardiopulmonary complications exhibited signs of clinical deterioration hours before the event; more than 80% of these patients could be identified approximately 24 hours before these serious adverse events [ 26 ]. In this way, identifying patients who can benefit from intensive care units becomes crucial [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol is unprecedented and of great relevance, as some studies [ 24 , 25 ] have already demonstrated that the implementation of clinical deterioration evaluation directly impacts nurses in three areas of competence: (1) evaluation and care of patients (through the detection of clinical deterioration and development of skills and knowledge); (2) referring patients (through knowledge of the language and lines of communication in the referral process and deciding whether to seek help); and (3) coping experiences. Studies have also demonstrated that most patients who required hospitalization in intensive care units or who experienced cardiopulmonary complications exhibited signs of clinical deterioration hours before the event; more than 80% of these patients could be identified approximately 24 hours before these serious adverse events [ 26 ]. In this way, identifying patients who can benefit from intensive care units becomes crucial [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) referring patients (through knowledge of the language and lines of communication in the referral process and deciding whether to seek help); and (3) coping experiences. Studies have also demonstrated that most patients who required hospitalization in intensive care units or who experienced cardiopulmonary complications exhibited signs of clinical deterioration hours before the event; more than 80% of these patients could be identified approximately 24 hours before these serious adverse events [26]. In this way, identifying patients who can benefit from intensive care units becomes crucial [26].…”
Section: Innovative Protocol For Nurse Training In Early Detection Of...mentioning
confidence: 99%
“…In order to overcome these shortcomings, Bleijenberg et al ( 31 ) suggest using structured methodological frameworks such as the Intervention Mapping (IM) that fulfills the Medical Research Council’s (MRC) quality criteria on intervention development ( 31 , 32 ). Although the use and reporting of IM approaches is prevalent in health and prevention research ( 34 39 ), there are only a limited number of comparable academic articles published in the field of (clinical) psychology ( 40 , 41 ). The current article’s objectives are therefore twofold: We aim to describe the development and theoretical underpinnings of a mechanism-based and needs-oriented intervention for inpatients with psychosis (MEBASp) treated in an acute psychiatric setting.…”
Section: Introductionmentioning
confidence: 99%